2019
DOI: 10.1001/jamapsychiatry.2019.2499
|View full text |Cite
|
Sign up to set email alerts
|

Association of Cytomegalovirus and Toxoplasma gondii Antibody Titers With Bipolar Disorder

Abstract: IMPORTANCE Infection-associated immune activation and inflammation are increasingly recognized in the pathophysiology of bipolar disorder.OBJECTIVE To determine whether antibodies to common infectious agents, including cytomegalovirus (CMV), Toxoplasma gondii, and measles, as well as the inflammatory marker C-reactive protein, in serum samples differ between patients with bipolar disorder and control individuals without bipolar disorder. DESIGN, SETTING, AND PARTICIPANTSIn this case-control study, antibody tit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 44 publications
(86 reference statements)
1
29
0
Order By: Relevance
“…Given the well-established association between MDD, stress, and inflammation [1,2], it is conceivable that HCMV may be more prone to reactivation in MDD populations. Indeed, HCMV has been associated with depression in at least 13 studies [40][41][42][43][44][45][46][47][48][49][50][51][52][53]. In our recent work, we found that HCMV infection was associated with reduced gray matter volume in participants with MDD but not healthy controls [54].…”
Section: Introductionmentioning
confidence: 67%
“…Given the well-established association between MDD, stress, and inflammation [1,2], it is conceivable that HCMV may be more prone to reactivation in MDD populations. Indeed, HCMV has been associated with depression in at least 13 studies [40][41][42][43][44][45][46][47][48][49][50][51][52][53]. In our recent work, we found that HCMV infection was associated with reduced gray matter volume in participants with MDD but not healthy controls [54].…”
Section: Introductionmentioning
confidence: 67%
“…In addition to risky behavior, T . gondii exposure has been found to be associated with mental health [ 7 , 44 ], which may in turn influence diet-related outcomes. The above mechanisms would explain a direct or indirect causal relationship between T .…”
Section: Resultsmentioning
confidence: 99%
“…While several studies have corroborated the hypothesis, others have consistently contradicted it based on relevant samples. 37,42,45 Nevertheless, it should be noted that both of the above described studies were based on neonatal blood samples, meaning that the antibodies probably originated from the mother, rather than the newborn's exposure to the parasite. Higher quality studies are indicated by more stars in each category.…”
Section: Bipolar Disordermentioning
confidence: 99%